The Influence of Good Corporate Governance Principles on Competitiveness of Companies Listed in the Stock Exchange of Thailand - Chankham, Panichar; Chemsripong, Sujinda (Ph.D. in Social Sciences Journal, 2024)
This research article aims to study the direct and indirect influence of good corporate governance practices on the competitiveness of listed companies on the Stock Exchange of Thailand (SET). The research model is quantitative research. The sampling group is a total of 293 listed companies in all industries except financial groups. The data collection questionnaire tool uses descriptive statistics using frequency values, percentages, and structural equation model analysis. And analyze the relationship path. Findings are as follows: The index measured acceptable consistency at a good level, with chi-square (χ²) = 58.48, χ²/df = 1.54, p-value = 0.017, GFI = 0.96, CFI = 0.99, AGFI = 0.94 and RMSA = 0.043 and a statistically significant operating variable (IMPE) of 0.98 at 0.05 purpose operating variables (IMPE) with a statistically significant positive direct influence of 0.66 and an OBJ with a statistically significant direct influence of 0.62 at 0.05 respectively.